2017
DOI: 10.1615/plasmamed.2018019503
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Interaction between a Helium Plasma Jet and Conductive (Metal)/ Non-Conductive (Dielectric) Targets

Abstract: Recent research in plasma biology proved that atmospheric pressure plasma jets (APPJs) have a biocidal effect, making them a promising alternative to traditional antimicapability of the APPJs, the streamer propagation, and the chemistry involved. The aim of this study is to investigate experimentally the effect of the target conductivity on the plasma characteristics: plasma jet propagation and reactive species production. The results show that the tions depend on the conductivity of the target. The results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…For plasma setups, the characteristics like emission, species generation, electrical field strength amplitude and even stability are impacted when a surface is put in close vicinity [9][10][11][12][13][14]. Thus, an increased interest has arisen in recent years in the investigation of interaction with a target made of liquid, dielectric or metal resembling specific application conditions [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For plasma setups, the characteristics like emission, species generation, electrical field strength amplitude and even stability are impacted when a surface is put in close vicinity [9][10][11][12][13][14]. Thus, an increased interest has arisen in recent years in the investigation of interaction with a target made of liquid, dielectric or metal resembling specific application conditions [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…When a target was grounded, the electric field significantly increased compared to when using a floating target. Yamada et al [36] and Kone et al [37] measured the spatial distributions of OH, N 2 + , O, and He by optical emission spectroscopy. [36,37] Darny et al [38] and Hofmans et al [39] reported experimental data for the electric field in an APPJ with and without a target.…”
mentioning
confidence: 99%
“…Fig. 5(b) highlights the main emission lines of the plasma jet flowing in air, commonly observed by many authors [38][39][40][41][42] on a reduced wavelength range (300-800nm). Two spectra were recorded in this work.…”
Section: B Plasma Diagnosticsmentioning
confidence: 63%
“…The characterization of piezo-plasma jet was made by optical emission spectroscopy and by bidimensional emission imaging. An optical spectrometer (HR2000+, Ocean Optics, Grating 1800mm-1, slit 10μm, 200 to 1100nm, maximal optical resolution 0.5nm) coupled to an optical fiber (core diameter 600μm) was used to identify the plasma emission lines [40]. The measurement was realized in order to identify the typical optical emissions of the carrier gas and the reactive species due to the ambient air.…”
Section: B Plasma Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation